Radix asparagi polyurea washed stone as well as preparation method and application thereof
By using the combination technology of asparagus polyurea transparent resin and stone particles, the asparagus polyurea water-washed stone with high adhesion and weather resistance, the existing problems of insufficient water-resistant, acid-resistant and alkali-resistant properties of stone-washed stone are solved, and the problem of insufficient water-resistant, acid-resistant and alkali-resistant properties of existing stone-washed stone is achieved. Stable construction and long-term use on different environments and substrates.
Patent Information
- Application Number
- CN202510052768.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing water-washed stone has poor water, acid and alkali resistance and insufficient adhesion. Especially when constructing on construction surfaces with large slopes, it is difficult to scrape, and even lead to sand and gravel falling off.
Asparagus polyurea transparent resin is used as the main component, and the asparagus polyurea water-washed stone with high adhesion and weather resistance is formed by combining dispersion and mixing with curing agent. The method includes mixing components A and components B of asparagus polyurea transparent resin in a certain proportion and stirring them thoroughly with the stone particles to form a resin system that wraps the stone particles.
It realizes high adhesion and excellent weather resistance of asparagus polyurea washing stone, and can maintain its performance under long-term outdoor exposure to the sun and soaking water. It is suitable for various base materials and can be used on different slopes and three-dimensional walls. construction.
Smart Images

Figure CN119461949A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to an asparagus polyurea washed stone and a preparation method and application thereof. Background Art
[0002] Washed stone is a decorative product that uses natural river pebbles, natural sea pebbles or gravel mixed with cement in a certain proportion and then applied to the base layer, and then flattened with a weight-bearing tool to clean the surface adhesive to expose the original appearance of the stone. There are two common methods for preparing washed stone: one is to first mix the mortar, color powder, and construction adhesive evenly, then add the stone and stir thoroughly, then spread, smooth, and pat out the slurry; the other is to first mix the mortar, spread, and smooth, then spread the stone by hand to make it even and dense, then flatten and pat out the slurry; after patting out the slurry, wait for about half an hour for the mortar to initially set, and then use a large sponge dipped in water to wipe off the cement slurry on the stone surface, so that the surface layer of the washed stone is exposed, and then it is cured for 3 to 7 days to meet the strength requirements of the washed stone.
[0003] However, these traditional methods of making washed stone have problems such as large amount of cement, high construction difficulty, difficulty in scraping and scrubbing, and easy weathering and cracking of cement. A Chinese invention patent application with publication number CN118307244A discloses a water-free washed stone and its preparation method, which includes the following raw materials in parts by weight: 110-125 parts of water, 2-4 parts of cellulose, 2-3 parts of bentonite, 2-3 parts of fungicide, 1-2 parts of pH adjuster, 1-2 parts of defoamer, 140-150 parts of silicone emulsion, 4-6 parts of ethylene glycol, 6-9 parts of C-2 film-forming aid, 3-5 parts of associative thickener, and 700-750 parts of gravel. Although the washed stone produced by this invention has good wear resistance, compressive strength and tensile strength, it has poor water resistance, acid resistance and alkali resistance (such as Figure 5 As shown in the figure, this is a major drawback for outdoor decorative washed stones that are often exposed to the sun and wind, or even soaked in water for a long time. In addition, the existing water-free washed stones have poor adhesion, especially when constructed on a construction surface with a slope of ≥25°. The washed stones have insufficient adhesion to the base layer, making it difficult to scrape, and even causing sand and gravel to fall off (such as Figure 6 as shown).
[0004] Based on these problems, the present invention has developed an asparagus polyurea washed stone with excellent water resistance, acid resistance, alkali resistance, weather resistance and strong adhesion, which can be applied to various base materials and can maintain various performances unaffected under long-term outdoor water immersion conditions; when performing scraping construction, it can be applied to base surfaces with different slopes and can even be constructed on 90° three-dimensional walls. Summary of the invention
[0005] The purpose of the present invention is to provide an asparagus polyurea washed stone with strong adhesion and excellent water and weather resistance, and a preparation method and application thereof, so as to solve one or more technical problems existing in the prior art and at least provide a beneficial solution or option.
[0006] To achieve the above objectives, the present invention adopts the following technical solutions.
[0007] A kind of asparagus polyurea washed stone consists of component A, component B and component C. In parts by mass, the composition of component A is as follows.
[0008] 40-45 parts of asparagus polyurea transparent resin.
[0009] Silane coupling agent 0.5~1 part
[0010] 2~4 parts of dewatering agent.
[0011] 0.1~1 part of anti-settling wax.
[0012] Dispersant 0.1~1 part.
[0013] Defoaming agent 0.1~0.5 parts.
[0014] 1~3 parts of hydrophilic fumed silica.
[0015] The composition of component B is as follows.
[0016] 42-49 parts of asparagine polyurea transparent resin curing agent.
[0017] 0.1~1 part of bentonite thixotropic agent.
[0018] Component C consists of 1500~2000 parts of stone particles.
[0019] In the present invention, by adding stone particles of different colors and controlling the ratio of stone particles of different color numbers and different coarsenesses, various asparagus polyurea washed stones can be formulated, and the styles are varied and adjustable; and the system has high hardness, wear resistance, and corrosion resistance, and is also suitable for roads or roofs that are stepped on by many people for a long time; the system has low formaldehyde and no radioactivity, and can be recycled at the same time, and the VOC content is ≤50g / L, which is environmentally friendly and healthy.
[0020] The preparation steps of the above-mentioned asparagus polyurea washed stone are as follows: 1) by weight, 1-3 parts of hydrophilic fumed silica, 40-45 parts of asparagus polyurea resin, 0.5-1 parts of silane coupling agent, 2-4 parts of dewatering agent, 0.1-1 parts of anti-settling wax, 0.1-1 parts of dispersant, and 0.1-0.5 parts of defoaming agent are dispersed and mixed uniformly at room temperature to obtain asparagus polyurea transparent resin component A; 2) by weight, 42-49 parts of asparagus polyurea resin curing agent and 0.1-1 parts of bentonite thixotropic agent are mixed uniformly to obtain asparagus polyurea transparent resin component B; 3) the asparagus polyurea transparent resin obtained in step 1) is mixed uniformly. The obtained asparagus polyurea transparent resin component A and the asparagus polyurea transparent resin component B obtained in step 2) are mixed and stirred evenly in a mass ratio of 1:0.8-1:1.2 to obtain an asparagus polyurea resin mixture, and then 100 parts of the asparagus polyurea resin mixture and 1500-2000 parts of stone particles are mixed and stirred evenly according to mass parts, so that the asparagus polyurea resin wraps all the stone particles to obtain an asparagus polyurea washed stone material; 4) the asparagus polyurea washed stone material obtained in step 3) is applied on the base surface, spread to a specified thickness with a tool, and pressed downward until it is flat to obtain the asparagus polyurea washed stone.
[0021] More preferably, in step 1), the dispersion is achieved by a disperser, and the dispersion speed of the disperser is controlled at 1000-1200 r / min.
[0022] More preferably, in step 3), after the asparagine polyurea transparent resin component A and the asparagine polyurea transparent resin component B are mixed and stirred evenly, the stone particles are added within 30 minutes and stirred evenly.
[0023] More preferably, in step 3), the stone particles are natural colored sand with a particle size of 3 to 6 mm, or sintered colored sand of the same specification.
[0024] On the other hand, the present invention also provides the use of the above-mentioned method for preparing asparagus polyurea washed stone in ground or wall construction.
[0025] On the other hand, the present invention also provides the use of the above-mentioned method for preparing asparagus polyurea washed stone in the construction of swimming pool or pond soaking water surface.
[0026] On the other hand, the present invention also provides the use of the above-mentioned method for preparing asparagus polyurea washed stone in the preparation of washed stone bricks.
[0027] The present invention adopts the above technical solution to have at least the following beneficial effects.
[0028] After actual production inspection, the asparagus polyurea washed stone prepared by the present invention has the following properties: it meets the test requirements of 6000h artificial weather aging resistance, has excellent weather resistance, and does not change color or fall off when used for long-term outdoor exposure; it meets the test requirements of one year of water resistance; it meets the test requirements of 720h of acid and alkali resistance, has excellent water resistance, acid resistance and alkali resistance, and does not change color, corrode or fall off when used in indoor and outdoor swimming pools, ponds, fish ponds and other scenes where it is soaked in water for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for describing the embodiments or the prior art are briefly introduced below.
[0030] Figure 1 Shown is a photo of the facade construction of the asparagus polyurea washed stone material prepared in Example 1 of the present invention.
[0031] Figure 2 Shown are photos of the water soaking test of the asparagus polyurea washed stone prepared in Example 1 of the present invention.
[0032] Figure 3 Shown are photos of the anti-sagging test of the asparagus polyurea washed stone material prepared in Example 1 of the present invention.
[0033] Figure 4 Shown is a photo of the anti-sagging test of the asparagus polyurea washed stone material in Comparative Example 5.
[0034] Figure 5 Shown are photos of a water soaking test of asparagus polyurea washed stone in the prior art.
[0035] Figure 6 Shown is a photo of the anti-sagging test of asparagine polyurea washed stone in the prior art. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the essence of the present invention, the specific implementation methods of the present invention are described in detail below with reference to the accompanying drawings. Example 1
[0037] A method for preparing asparagus polyurea washed stone, the preparation steps of which are as follows.
[0038] 1) According to the mass percentage, 2 parts of hydrophilic fumed silica, 43 parts of asparagine polyurea resin, 0.8 parts of silane coupling agent, 3 parts of dewatering agent, 0.5 parts of anti-settling wax, 0.5 parts of dispersant and 0.3 parts of defoaming agent are placed in a disperser, and the above raw materials are dispersed and mixed uniformly at a speed of 1100r / min at room temperature to obtain asparagine polyurea transparent resin component A.
[0039] 2) 45 parts of asparagine polyurea resin curing agent and 0.5 parts of bentonite thixotropic agent were mixed uniformly by mass to obtain asparagine polyurea transparent resin component B.
[0040] 3) The asparagus polyurea transparent resin component A obtained in step 1) and the asparagus polyurea transparent resin component B obtained in step 2) are mixed in a mass ratio of 1:1 and stirred evenly to obtain an asparagus polyurea resin mixture, and then 100 parts of the asparagus polyurea resin mixture are mixed with 1800 parts of natural colored sand with a particle size of 5 mm by mass within 30 minutes and stirred evenly, so that the asparagus polyurea resin wraps all stone particles to obtain an asparagus polyurea washed stone material.
[0041] 4) Apply the asparagus polyurea washed stone material obtained in step 3) on the base surface, spread it to a specified thickness with a trowel, and press it down until it is flat to obtain the asparagus polyurea washed stone.
[0042] Figure 1 The figure shows a schematic diagram of the asparagus polyurea washed stone material obtained in this embodiment being constructed on a facade. It can be seen from the figure that the asparagus polyurea washed stone material does not drip or scatter during the construction on the facade.
[0043] Figure 2 The figure shows the soaking schematic diagram of the asparagus polyurea washed stone obtained in this embodiment. It can be seen from the figure that there is no foaming and no color change after soaking in water for 168 hours, which meets the application requirements of long-term soaking environment. Example 2
[0044] A method for preparing asparagus polyurea washed stone, the preparation steps of which are as follows.
[0045] 1) According to the mass proportion, 1 part of hydrophilic fumed silica, 40 parts of asparagine polyurea resin, 0.5 parts of silane coupling agent, 2 parts of dewatering agent, 0.3 parts of anti-settling wax, 0.1 parts of dispersant and 0.1 parts of defoaming agent are placed in a disperser, and the above raw materials are dispersed and mixed uniformly at a speed of 1000 r / min at room temperature to obtain asparagine polyurea transparent resin component A.
[0046] 2) 42 parts of asparagine polyurea resin curing agent and 0.2 parts of bentonite thixotropic agent were mixed uniformly by mass to obtain asparagine polyurea transparent resin component B.
[0047] 3) The asparagus polyurea transparent resin component A obtained in step 1) and the asparagus polyurea transparent resin component B obtained in step 2) are mixed and stirred at a mass ratio of 1:1.2 to obtain an asparagus polyurea resin mixture, and then 100 parts of the asparagus polyurea resin mixture are mixed and stirred with 1500 parts of natural colored sand stone particles with a particle size of 6 mm by mass within 30 minutes, so that the asparagus polyurea resin wraps all the stone particles to obtain an asparagus polyurea washed stone material.
[0048] 4) Apply the asparagus polyurea washed stone material obtained in step 3) on the base surface, spread it to a specified thickness with a trowel, and press it down until it is flat to obtain the asparagus polyurea washed stone. Example 3
[0049] A method for preparing asparagus polyurea washed stone, the preparation steps of which are as follows.
[0050] 1) According to the mass percentage, 3 parts of hydrophilic fumed silica, 45 parts of asparagine polyurea resin, 1 part of silane coupling agent, 4 parts of dewatering agent, 1 part of anti-settling wax, 1 part of dispersant, and 0.5 parts of defoaming agent are placed in a disperser, and the above raw materials are dispersed and mixed uniformly at a speed of 1200r / min at room temperature to obtain asparagine polyurea transparent resin component A.
[0051] 2) 49 parts of asparagine polyurea resin curing agent and 1 part of bentonite thixotropic agent were mixed uniformly by mass to obtain asparagine polyurea transparent resin component B.
[0052] 3) The asparagus polyurea transparent resin component A obtained in step 1) and the asparagus polyurea transparent resin component B obtained in step 2) are mixed in a mass ratio of 1:0.8 and stirred evenly to obtain an asparagus polyurea resin mixture, and then 100 parts of the asparagus polyurea resin mixture are mixed with 2000 parts of sintered colored sand stone particles with a particle size of 3 mm by mass within 30 minutes and stirred evenly, so that the asparagus polyurea resin wraps all the stone particles to obtain an asparagus polyurea washed stone material.
[0053] 4) Apply the asparagus polyurea washed stone material obtained in step 3) on the base surface, spread it to a specified thickness with a trowel, and press it down until it is flat to obtain the asparagus polyurea washed stone.
[0054] In order to better reflect the technical advancement of the present invention, the inventors also conducted comparative experiments and performance tests.
[0055] Comparative Example 1: This comparative example is basically the same as Example 1, except that the amount of the silane coupling agent is changed to 5 parts.
[0056] Comparative Example 2: This comparative example is basically the same as Example 1, except that the amount of the silane coupling agent is changed to 0.1 parts.
[0057] Comparative Example 3: This comparative example is basically the same as Example 1, except that the amount of hydrophilic fumed silica is changed to 5 parts.
[0058] Comparative Example 4: This comparative example is basically the same as Example 1, except that the amount of bentonite thixotropic agent is changed to 5 parts.
[0059] Comparative Example 5: This comparative example is basically the same as Example 1, except that the amount of hydrophilic fumed silica is changed to 0.5 parts.
[0060] Comparative Example 6: This comparative example is basically the same as Example 1, except that the amount of natural colored sand is changed to 2500 parts.
[0061] Comparative Example 7: This comparative example is basically the same as Example 1, except that the amount of natural colored sand is changed to 1000 parts.
[0062] Performance test comparison.
[0063] Table 1. Properties of component A of asparagus polyurea transparent resin project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Appearance Transparent liquid Transparent liquid Transparent liquid Transparent liquid Transparent liquid <![CDATA[Specific gravity (g / cm 3 )]]> 1.05 1.03 1.06 1.05 1.05 <![CDATA[Viscosity·10 3 (cps, 25 °C)]]> 2.5 1.8 3.8 15 1.8 Solid content (%) 99 98.8 99.3 99.2 98.8 Surface drying time / h 0.5 0.5 0.5 0.5 0.5 Applicable period / h 0.5 0.5 0.5 0.5 0.5 Adhesion (concrete) / MPa 9.97 10.1 9.82 - 1.1 .
[0064] As can be seen from Table 1, the viscosity of the asparagus polyurea transparent resin component A at 25°C is 1.8×10 3 cps to 3.8×10 3 cps, the adhesion test can reach 9.82-10.1MPa, compared with the adhesion of traditional washed stone on the market which is about 2MPa, it can be seen that the asparagus polyurea transparent resin component A in the present invention has excellent adhesion and can be applied to a variety of substrates with a wide range of applications.
[0065] When silane coupling agent ≥5 parts is added (Comparative Example 1), the viscosity of the system increases dramatically, reaching 15×10 3 cps, the whole system tends to be paste-like, has extremely poor flow properties and is difficult to apply.
[0066] When silane coupling agent is added in an amount of ≤0.1 parts (Comparative Example 2), the adhesion test of the system is 1.1 MPa, and the adhesion is reduced, which does not meet the requirement of traditional washed stone adhesion ≥2 MPa.
[0067] Table 2 Physical properties of the system after mixing the asparagus polyurea transparent resin component A and the asparagus polyurea transparent resin component B project Example 1 Comparative Example 3 Comparative Example 4 Comparative Example 5 Hardness (Shore A) 90 120 120 ≤70 Adhesion (concrete) / MPa 9.97 4.56 4.58 2.75 Water-impermeability (0.4MPa, 2h) impermeable impermeable impermeable permeable Wear resistance / mg 3.8 8.9 8.7 39 Impact strength / kg*m 2.4 0.8 0.7 0.4 Tensile strength / MPa 45 10 9 5 Elongation / % 750 385 385 235 Artificial weathering resistance / h No discoloration after 6000h, gloss loss <2, chalking <1 No discoloration after 6000h, gloss loss <2, chalking <1 No discoloration after 6000h, gloss loss <2, chalking <1 6000h color change, gloss loss ≥ 2, powdering ≥ 1 Water resistance 365d: No bubbles, no discoloration, no shedding 365d: No bubbles, no discoloration, no shedding 365d: No bubbles, no discoloration, no shedding 365d: blistering, discoloration, shedding Acid resistance 720h no corrosion, no discoloration, no shedding 720h no corrosion, no discoloration, no shedding 720h no corrosion, no discoloration, no shedding 720h corrosion, discoloration, and shedding Alkali resistance (40% NaOH) 720h no corrosion, no discoloration, no shedding 720h no corrosion, no discoloration, no shedding 720h no corrosion, no discoloration, no shedding 720h corrosion, discoloration, and shedding Salt spray resistant No discoloration or shedding after 6000h No discoloration or shedding after 6000h No discoloration or shedding after 6000h 6000h color change, shedding Oil resistance (motor oil) No discoloration or shedding for 720h No discoloration or shedding for 720h No discoloration or shedding for 720h 720h color change, shedding Tear strength / N / mm 100 45 45 20 .
[0068] It can be seen from Table 2 that when ≥5 parts of hydrophilic fumed silica is added (Comparative Example 3), or ≥5 parts of bentonite thixotropic agent is added to component B (Comparative Example 4), the viscosity of the system will increase dramatically, affecting the flow properties of the system, resulting in easy agglomeration and uneven spreading during construction, thereby reducing the adhesion and elasticity of the system, resulting in a decrease in the impact, tensile, tear and other strength performance tests of the system.
[0069] When the hydrophilic fumed silica is added at ≤0.5 parts (Comparative Example 5), it may cause sagging, agglomeration or uneven thickness when the base surface is uneven or vertical construction is carried out, such as Figure 4 As shown. In comparative example 5, when the performance test was carried out in the thicker area of the system, all the performances were basically consistent with those of Example 1; when the performance test was carried out in the thinner area of the system, the hardness, adhesion, impact strength, tensile strength, tear strength and elongation at break of the system all decreased; and the water resistance, acid resistance, alkali resistance, salt spray resistance, oil resistance and artificial weather aging resistance all showed discoloration and shedding. The present invention can give the system strong pseudoplastic flow characteristics, thereby producing excellent anti-sagging effect during vertical construction, and at the same time can ensure the excellent self-leveling performance of the system, avoid surface defects, and prevent shrinkage. Figure 3 shown.
[0070] Table 3. Physical properties of asparagus polyurea washed stone materials project Example 1 Example 2 Comparative Example 6 Comparative Example 7 Adhesion (concrete) / MPa 9.97 9.97 1.5 15 Wear resistance / mg ≤30 ≤40 ≤40 ≤40 Artificial weathering resistance / h No discoloration after 6000h, gloss loss <2, chalking <1 No discoloration after 6000h, gloss loss <2, chalking <1 6000h color change, gloss loss ≥ 2, powdering ≥ 1 No discoloration after 6000h, gloss loss <2, chalking <1 Water resistance 365d: No bubbles, no discoloration, no shedding 365d: No bubbles, no discoloration, no shedding 365d: blistering, discoloration, shedding 365d: No bubbles, no discoloration, no shedding Acid resistance No corrosion, discoloration or shedding for 720h No corrosion, discoloration or shedding for 720h 720h corrosion, discoloration, and shedding No corrosion, discoloration or shedding for 720h Alkali resistance (40% NaOH) No corrosion, discoloration or shedding for 720h No corrosion, discoloration or shedding for 720h 720h corrosion, discoloration, peeling No corrosion, discoloration or shedding for 720h Salt spray resistant No discoloration or shedding for 6000h No discoloration or shedding for 6000h 6000h color change, shedding No discoloration or shedding for 6000h Oil resistance (motor oil) No discoloration or shedding for 720h No discoloration or shedding for 720h 720h color change, shedding No discoloration or shedding for 720h .
[0071] The asparagus polyurea washed stone material prepared by the present invention is added with 1500-2000 parts of natural colored sand (or sintered sand) of different colors, and the ratio of sand of different colors and coarseness is controlled, so that various asparagus polyurea washed stones with varied styles can be prepared, and the styles are changeable and adjustable; and the system has high hardness, wear resistance, and corrosion resistance, and is also suitable for long-term multi-person trampling on roads or roofs; the system has low formaldehyde, no radioactivity, and can be recycled, and the VOC content is ≤50g / L, which is environmentally friendly and healthy.
[0072] When ≥ 2500 parts of natural colored sand (or sintered sand) are added (Comparative Example 6), the base material mixed with components A and B cannot wrap the sand, resulting in insufficient compactness of the system, loose construction, and difficulty in construction; at the same time, the adhesion is affected, and the adhesion to the base surface does not meet the requirements; the exposed natural colored sand (or sintered sand) changes color and falls off during water resistance, acid resistance, alkali resistance, salt spray resistance, oil resistance, and artificial climate aging resistance tests.
[0073] When natural colored sand (or sintered sand) is added in an amount of ≤1000 parts (Comparative Example 7), the adhesion is increased, and all performance tests are the same as those in Example 1. However, at this time, the proportion of the base material mixed with A and B in the system is too high, resulting in waste of the base material and increased costs.
[0074] It should be noted that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0075] The above embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. The parts not described in the specific embodiments are all prior art or common knowledge.
Claims
1. A method for preparing asparagus polyurea washed stone, characterized in that: Here are the steps: 1) By mass, 1-3 parts of hydrophilic fumed silica, 40-45 parts of asparagine polyurea resin, 0.5-1 parts of silane coupling agent, 2-4 parts of dehydrating agent, 0.1-1 parts of anti-settling wax, 0.1-1 parts of dispersant, and 0.1-0.5 parts of defoaming agent are dispersed and mixed uniformly at room temperature to obtain asparagine polyurea transparent resin component A; 2) 42-49 parts of asparagine polyurea resin curing agent and 0.1-1 parts of bentonite thixotropic agent are mixed uniformly by mass to obtain asparagine polyurea transparent resin component B; 3) The asparagine polyurea transparent resin component A obtained in step 1) and the asparagine polyurea transparent resin component B obtained in step 2) are mixed and stirred at a mass ratio of 1:0.8 to 1:1.2 to obtain an asparagine polyurea resin mixture, and then 100 parts of the asparagine polyurea resin mixture are mixed and stirred with 1500 to 2000 parts of stone particles by mass, so that the asparagine polyurea resin wraps all the stone particles to obtain an asparagine polyurea washed stone material; 4) Apply the asparagine polyurea washed stone material obtained in step 3) on the base surface, spread it to a specified thickness with a tool, and press it down until it is flat to obtain the asparagine polyurea washed stone.
2. The method for preparing asparagus polyurea washed stone according to claim 1, characterized in that: In step 1), dispersion is achieved by a disperser, and the dispersion speed of the disperser is controlled at 1000~1200r / min.
3. The method for preparing asparagus polyurea washed stone according to claim 1, characterized in that: In step 3), after the asparagus polyurea transparent resin component A and the asparagus polyurea transparent resin component B are mixed and stirred evenly, the stone particles are added within 30 minutes and stirred evenly.
4. The method for preparing asparagus polyurea washed stone according to claim 1, characterized in that: In step 3), the stone particles are natural colored sand with a particle size of 3 mm to 6 mm.
5. The method for preparing asparagus polyurea washed stone according to claim 1, characterized in that: In step 3), the stone particles are sintered colored sand with a particle size of 3 mm to 6 mm.
6. Asparagus polyurea washed stone obtained by the preparation method of asparagus polyurea washed stone as claimed in any one of claims 1 to 5.
7. Application of the preparation method of asparagus polyurea washed stone as described in any one of claims 1 to 5 in ground or wall construction.
8. Use of the preparation method of asparagus polyurea washed stone as claimed in any one of claims 1 to 5 in the construction of swimming pool or pond soaking water surface.
9. Use of the method for preparing asparagus polyurea washed stone as claimed in any one of claims 1 to 5 in preparing washed stone bricks.
Citation Information
Patent Citations
Washing-free washing stone and preparation method thereof
CN118307244A
Weather-resistant anticorrosive polyurea coating material as well as preparation and use methods thereof
CN103834282A
Exposed aggregate concrete and construction method thereof
CN109761538A
Radix asparagi polyurea millstone floor composition
CN119191759A
Thin-layer paving base material and pavement structure
JP1999001904A